Respuesta :

Answer:

To find \( f(0) \), \( f(12) \), and \( f(d) \) in the function \( f(x) = 2x - 1 \):

1. \( f(0) \):

Substitute \( x = 0 \) into the function:

\[ f(0) = 2(0) - 1 = 0 - 1 = -1 \]

2. \( f(12) \):

Substitute \( x = 12 \) into the function:

\[ f(12) = 2(12) - 1 = 24 - 1 = 23 \]

3. \( f(d) \):

Since \( f(d) \) is not a specific value like \( f(0) \) or \( f(12) \), we leave it in terms of \( d \):

\[ f(d) = 2d - 1 \]

So, \( f(0) = -1 \), \( f(12) = 23 \), and \( f(d) = 2d - 1 \).